2005
DOI: 10.1074/jbc.m414238200
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of ErbB Family and Cell Survival Signaling after Knock-down of ErbB2 in Colon Cancer Cells

Abstract: The role of the ErbB family in supporting the malignant phenotype was characterized by stable transfection of a single chain antibody (ScFv5R) against ErbB2 containing a KDEL endoplasmic reticulum retention sequence into GEO human colon carcinoma cells. The antibody traps ErbB2 in the endoplasmic reticulum, thereby down-regulating cell surface ErbB2. The transfected cells showed inactivation of ErbB2 tyrosine phosphorylation and reduced heterodimerization of ErbB2 and ErbB3. This resulted in greater sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 63 publications
3
21
0
Order By: Relevance
“…In addition to this escape from inhibition of signal transduction through a mechanism involving incomplete inhibition of a heterodimerized receptor, we have shown that inhibition of one receptor can be compensated for by the increased expression and activation of another receptor (36). ErbB2 inactivation by stable transfection of a single chain antibody against ErbB2 resulted in the inactivation of ErbB2 tyrosine phosphorylation and reduced heterodimerization of ErbB2 and ErbB3.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this escape from inhibition of signal transduction through a mechanism involving incomplete inhibition of a heterodimerized receptor, we have shown that inhibition of one receptor can be compensated for by the increased expression and activation of another receptor (36). ErbB2 inactivation by stable transfection of a single chain antibody against ErbB2 resulted in the inactivation of ErbB2 tyrosine phosphorylation and reduced heterodimerization of ErbB2 and ErbB3.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ZD1839, a specific EGFR tyrosine kinase inhibitor, has been reported to inhibit the growth of ErbB2-overexpressing breast cancer cells, possibly by sequestration of ErbB2 and ErbB3 receptors in an inactive heterodimer configuration with EGFR (47). Another group also reported that elimination of ErbB2 signaling resulted in an increase in EGFR expression and activation and that its increased activation contributed to sustained cell survival (48). Changes in receptor-receptor interactions between ErbB family members and compensatory changes in the ErbB family after inhibition of one of its members are of potential importance in optimizing current EGFR family -directed therapies for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Integrin β4 signaling also promotes ErbB2-mediated cell proliferation in a mammary tumor model [32]. Since ErbB2 exerts pro-survival effects in colon carcinoma cell lines [33,34], the effects of PTHrP on colon cancer cell proliferation in vitro and on xenograft growth in vivo may be mediated via the integrin β4/ErbB2 pathway.…”
Section: Discussionmentioning
confidence: 99%